THE INFLUENCE OF THE HOT-FIT MODEL ON INFORMATION SYSTEM IMPLEMENTATION IN THE LIVIN’ BY MANDIRI APPLICATION - Vivit Marlia Sosalina; Irwansyah; Fadli (RADJA PUBLIKA, 2026)
This study aims to examine the influence of the HOT-Fit model on the implementation of information systems in the Livin' by Mandiri application. Different from previous studies that discussed the use of mobile banking in Indonesia, but with a different focus and scope. In this study, analyzing the influence of user satisfaction factors on the Livin' by Mandiri application, the HOT model is used because it has a holistic approach in distributing various factors that influence technology acceptance. This study uses a quantitative approach with a survey design. The population in this study includes all Bank Mandiri customers domiciled in Bengkulu City. Sample selection in this study was carried out using non-probability sampling, using the convenience sampling method, using the Hair et al. method, obtained a sample of 240 people. The data source for this study uses primary data with data collection techniques through the distribution of questionnaires at branch offices and through Google Form links. Data analysis was carried out using SmartPLS software. The results of the study indicate that the success of the implementation of the Livin' by Mandiri application is not only determined by technological aspects, but also by human, organizational, and technological factors, as described in the HOT-Fit model. Dimensions related to system usability and user satisfaction play the most important role in generating net benefits, while service and system quality need to be supported by a fit with user needs and experience to deliver optimal impact. This research supports the implementation of the HOT-Fit model in mobile banking implementation, while also providing recommendations for Bank Mandiri to optimize the development of digital services that focus on user needs.